Observation of reactive shear layer modulation associated with high-frequency transverse thermoacoustic oscillations in a gas turbine reheat combustor experiment. Issue 1 (March 2022) - McClure, Jonathan; Berger, Frederik M.; Bertsch, Michael; Schuermans, Bruno; Sattelmayer, Thomas
This paper presents the investigation of high-frequency thermoacoustic oscillations and associated flame dynamics in an experimental gas turbine reheat combustor at atmospheric pressure. Examination of dynamic pressure measurements reveals bursts of high-frequency periodic oscillations which appear randomly amidst stochastic fluctuations in the reheat combustor. Analysis of the flame dynamics during these bursts of periodic behaviour reveals that increased heat release in the reactive shear layers of the reheat flame is associated with greater thermoacoustic driving potential. This redistribution of heat release is likely due to the stochastic nature of auto-ignition kernel formation. To determine the underlying flame-acoustic coupling mechanism behind the driving potential, phase-resolved flame dynamics over the acoustic cycle are investigated which reveal the presence of an oscillatory heat release pattern associated with the first transverse eigenmode. An in-phase interaction between the acoustic field and these heat release oscillations in the shear layer regions indicates that this phenomenon likely constitutes a thermoacoustic driving mechanism. This is an important step towards the development of models for high-frequency thermoacoustic driving mechanisms relevant to reheat combustion systems, which will allow accurate prediction and mitigation of thermoacoustic instabilities in future designs.